Kinematics and geomorphological changes of a destabilising rock glacier captured from close-range sensing techniques (Tsarmine rock glacier, Western Swiss Alps) - Vivero, Sebastián; Hendrickx, Hanne; Frankl, Amaury; Delaloye, Reynald; Lambiel, Christophe (Frontiers in Earth Science, 2022)
Accurately assessing landform evolution and quantifying rapid environmental changes are gaining importance in the context of monitoring techniques in alpine environments. In the European Alps, glaciers and rock glaciers are among the most characteristic cryospheric components bearing long and systematic monitoring periods. The acceleration in rock glacier velocities and the onset of destabilization processes, mainly since 1990, have raised several concerns due to the potential effects on the high alpine natural and anthropic environments. This study presents a combination of uncrewed aerial vehicle (UAV) and terrestrial laser scanning (TLS) surveys for monitoring the current changes on the quickly accelerating, destabilised Tsarmine rock glacier in the Arolla Valley, Western Swiss Alps, delivering a considerable volume of debris to a steep torrential gully. High-resolution digital elevation models (DEMs) and orthomosaics are derived from UAV image series combined with structure from motion (SfM) photogrammetry techniques. Multitemporal orthomosaics are employed for measuring spatially continuous rock glacier kinematics using image matching algorithms. Superficial displacements are evaluated with simultaneous in-situ differential global navigation satellite system (GNSS) measurements. Elevation and volume changes are computed from TLS and UAV-derived DEMs at similar periods. Between June 2017 and September 2019, both datasets showed a similar elevation change pattern and surface thinning rates of 0.15 ± 0.04 and 0.16 ± 0.03 m yr-1, respectively. Downward of a rupture zone developing about 150 m above the front, the rock glacier doubled its overall velocity during the study period, from around 5 m yr-1 between October 2016 and June 2017 to more than 10 m yr-1 between June and September 2019. The kinematic information reveals striking differences in the velocity between the lower and upper rock glacier sections. The monitoring approach based on close-sensing techniques provides accurate surface velocity and volume change information, allowing an enhanced description of the current rock glacier dynamics and its surface expression.